Neurocutaneous Melanosis in Association With Large Congenital Melanocytic Nevi in Children: A Report of 2 Cases With Clinical, Radiological, and Pathogenetic Evaluation - Chen, Lei; Zhai, Liqin; Al-Kzayer, Lika'a Fasih Y.; Sarsam, Shamil Naji; Liu, Tingting; Alzakar, Riyadh H.; Nakazawa, Yozo (Frontiers in Neurology, 2019)
Background: Melanocytic nevi present at birth, or within the first few months of life, are defined as congenital melanocytic nevi (CMN). Neurocutaneous melanosis (NCM) is a rare disorder, represents pigment cell tumors of the leptomeninges, and occurs in association with large or multiple CMN. NCM carries an extremely poor prognosis. NRAS and BRAFV600E genetic mutations were reported in CMN. Our aim was to report 2 rare cases of NCM associated with large-sized CMN. Materials and Methods: Two cases were enrolled, a 19-month-old boy with multiple satellite and giant CMN (GCMN); and a 57-month-old girl with large CMN (LCMN). Both patients had central nervous system (CNS) symptoms, and therefore, were studied from clinical, radiological, and immunohistopathological aspects. Cytogenetic study was done for one of them. Results: Both patients had CMN located in the head/neck, with no cutaneous melanoma. MRI was the most reliable method for early detection of NCM. NCM was proved in the 2 studied cases by immunohistopathology performed after surgery. The boy with GCMN carried NRAS mutation at codon 61, in addition to the characteristic facial features relevant to RASopathies. Both patients died despite surgical intervention. Conclusion: Our report highlights the need for pediatricians to be alert to the risk of NCM in association with CMN, especially when a CMN lesion is large, or there are multiple satellite lesions, or the nevus location is at the head or neck. Moreover, in the setting of CMN, the absence of skin melanoma does not exclude the presence of NCM.